2015
DOI: 10.5223/pghn.2015.18.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Celiac Disease and Dietary Adherence to Gluten-Free Diet among Saudi Children

Abstract: PurposeTo describe the clinical characteristics of celiac disease (CD) among Saudi children and to determine the adherence rate to gluten free diet (GFD) and its determinant factors among them.MethodsA cross-sectional study was conducted, in which all the families registered in the Saudi Celiac Patients Support Group were sent an online survey. Only families with children 18 years of age and younger with biopsy-confirmed CD were included.ResultsThe median age of the 113 included children was 9.9 years, the med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 18 publications
4
33
2
Order By: Relevance
“…The majority of our patients were women (68.6%), which was consistent with other studies, in which a slight predominance of females was observed [ 12 , 17 20 , 22 , 24 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…The majority of our patients were women (68.6%), which was consistent with other studies, in which a slight predominance of females was observed [ 12 , 17 20 , 22 , 24 , 26 ].…”
Section: Discussionsupporting
confidence: 93%
“…One or two decades ago, recurrent abdominal pain was rarely associated with celiac disease and for this presentation, serology screening was not considered to be justified (17). Later, this became one of the frequently seen clinical presentation in Western European countries, North America (6,(18)(19)(20) and other geographical areas (21,22) as a single clinical manifestation or in association with other symptoms. In the study of Khatib that looked at a group of celiac children recently diagnosed (2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013) in United States, abdominal pain was reported in higher percentages than diarrhea, being the most frequent digestive symptom (23).…”
Section: Discussionmentioning
confidence: 99%
“…We recently have shown that the compliance to GFD among Saudi children is relatively poor (62%) compared to other parts of the world [ 10 ]. As there are no local data looking for the socio-economic impact of GFD on celiac patients, we aimed, in the present study, to examine the socio-economic impact of GFD on Saudi children with CD and their families.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire consisted of four sections: the first section inquired about the demographic data of the child and family, the second section was on diagnostic details, while the third section had questions about family knowledge about GFD, its effect on the child's symptoms and the compliance of the child. The data from the previous 3 sections was recently published elsewhere [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation